Wpływ polityki społecznej na zmiany w świadomości mieszkańców wsi - Zakrzewski, Stanisław (Wydział Prawa i Administracji UAM, 1983)
In the years of 1979 - 1980 the author, together with his team was engaged in research works aimed at presenting the effect of social policy on an improvement of living conditions of aging farmers. Farmers inhabiting 29 communes in 11 districts in Wielkopolska, Kujawy regions and in the Western and (Northern (Regained) Territories were submitted to the survey investigation. Changes in a consciousness of country dwellers effected by social policy were one of the objects of the research. The article elaborates this problem as well. The territorial, chronological and material scope of research and source materials used are presented in the first part of the article. Next, the most important, in the author's opinion, trends of changes in a consciousness of country dwellers are described i.e.: — departure from treating land posessing and its amounts as an indicator of social position and authority of a farmer in his Village community, — changes in a traditional model of farmer's family, — creating wider oportunities for individuai farmers to participate in the socio- political life of our country, — appreciation of farmers' labor and increase in their professional prestige. Particular statements are illustrated with opinions of individual farmers and of administration and party apparatus workers in communes collected in the survey study.
The effect of social policies on changes in a consciousness of country dwellers